Overexpression of tissue inhibitor of matrix metalloproteinases-1 (TIMP-1) in mice does not affect adipogenesis or adipose tissue development - Demeulemeester, Diego; Scroyen, Ilse; Voros, Gabor; Snoeys, Jan; De Geest, Bart; Collen, Désiré; Lijnen, H. Roger (Thrombosis and Haemostasis, 2006)
In order to evaluate a potential functional role of tissue inhibitor of matrix metalloproteinases-1 (TIMP-1) in development of obesity, we studied the effect of overexpression of human TIMP-1 (hTIMP-1) in C57Bl/6J mice in vivo and in 3T3-F442A preadipocytes in vitro. Stable long-term overexpression of hTIMP-1 in mice was achieved by adenoviral gene transfer, yielding plasma levels exceeding 250 ng/ml at eight weeks after injection. Mice overexpressing hTIMP-1 and kept on a high fat diet for 14 weeks had body weights, adipose tissue weights, and adipocyte diameters that were somewhat, but not significantly, lower than those of control mice. Similar observations were made after overexpression of hTIMP-1 in mice with lipectomy of the subcutaneous adipose tissue, kept on a high fat diet for 20 weeks. In both in vivo models, blood vessels in the adipose tissues were significantly smaller after hTIMP-1 gene transfer than in control mice. Overexpression of hTIMP-1 in 3T3-F442A preadipocytes had no effect on their subsequent differentiation into mature adipocytes. Thus, overexpression of hTIMP-1 in mice had no significant effect on ongoing adipogenesis or adipose tissue development, although the blood vessel size in adipose tissues was reduced.
Keywords: Tissue inhibitor of metalloproteinase-1; TIMP-1; obesity; adipose tissue; adipogenesis